Carrier Modulation of Ambipolar Few‐Layer MoTe2 Transistors by MgO Surface Charge Transfer Doping. (15th December 2017) - Luo, Wei; Zhu, Mengjian; Peng, Gang; Zheng, Xiaoming; Miao, Feng; Bai, Shuxin; Zhang, Xue‐Ao; Qin, Shiqiao
Abstract: Semiconducting molybdenum ditelluride (2H‐MoTe2 ), a fast‐emerging 2D material with an appropriate band gap and decent carrier mobility, is configured as field‐effect transistors and is the focus of substantial research interest, showing hole‐dominated ambipolar characteristics. Here, carrier modulation of ambipolar few‐layer MoTe2 transistors is demonstrated utilizing magnesium oxide (MgO) surface charge transfer doping. By carefully adjusting the thickness of MgO film and the number of MoTe2 layers, the carrier polarity of MoTe2 transistors from p‐type to n‐type can be reversely controlled. The electron mobility of MoTe2 is significantly enhanced from 0.1 to 20 cm 2 V −1 s −1 after 37 nm MgO film doping, indicating a greatly improved electron transport. The effective carrier modulation enables to achieve high‐performance complementary inverters with high DC gain of >25 and photodetectors based on few‐layer MoTe2 flakes. The results present an important advance toward the realization of electronic and optoelectronic devices based on 2D transition‐metal dichalcogenide semiconductors. Abstract : The MoTe2 transistors are electron doped by magnesium oxide (MgO) surface charge transfer doping. The electron mobility of MoTe2 is significantly enhanced from 0.1 to 20 cm 2 V −1 s −1 after 37 nm MgO doping. The effective carrier modulation enables to achieve high‐performance complementary inverters with high DC gain of >25 and photodetectors based on few‐layer MoTe2 flakes.